Subhash Bose: India's first prime minister ? - Singh, U. V. (New Delhi Pentagon Press, 2017)
Indians' relationship with Subhash Chandra Bose, both at thought as well as dialogue level, has been deeply emotional. This book examines Bose's work and influence. This is not a biography but a fan's tribute to India's greatest revolutionary.
Keywords: History-India; India Independence-History